PERLINDUNGAN KONSUMEN TERHADAP PRODUK PANGAN KEMASAN PELAKU UMKM YANG TIDAK MENCANTUMKAN LABEL PANGAN - Hendri, Hendri; Oktarina, Neneng (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
Basically, consumers need law care universally. The care to consumers materially and formally is very important, because the progress of science and technology become rule on productivity and efficiency of producing on goods and service produced in reaching the purposes of effort.The problem in this study are: First, how is the care of consumers to products of food by agents of small and middle effort (UMKM) who unlabelled food based on BPOM in Bukittinggi City? Second, how is the responsibility of UMKM who unlabelled food based on BPOM to consumers in Bukittinggi City?The specification of this research is descriptive analytic. The method uses in this research is the normative and juridical empiric method. The techniques of collecting data uses are field study by interviewing for the primary data and library study for the secondary data. Then, the data analyzed qualitatively in descriptive analysis form.From the research results obtained several conclusions: First, the care of consumers to products of food by agents of small and middle effort (UMKM) who unlabelled food based on BPOM in Bukittinggi City can be done with many instruments, such as civil law instruments, criminal law instruments and also administration instruments. Second, the responsibility of UMKM who unlabelled food based on BPOM to consumers in Bukittinggi City is ready to be given sanction on the contrary done. The contrary by the agents of effort on the determination of label can be given responsibly or sanction civilly, criminal sanction, and administration sanction. The sanction of civil and criminal sometimes ineffectively withoutadministration sanctions.